The Role of Epigenetics in Plant Adaptation to Environmental Stress - Hamdan, Salma; Al-Fayez, Mazen; Chahine, Alaa (Research of Scientia Naturalis, 2025)
Epigenetics plays a crucial role in how plants adapt to environmental stressors such as drought, salinity, and extreme temperatures. Understanding the mechanisms behind epigenetic modifications can provide insights into plant resilience and survival strategies in changing environments. This study aims to investigate the role of epigenetic mechanisms in plant adaptation to various environmental stressors. By examining specific epigenetic modifications and their effects on gene expression, the research seeks to elucidate the pathways through which plants respond to stress. A combination of field experiments and laboratory analyses was employed to study epigenetic changes in selected plant species exposed to different environmental stress conditions. Techniques such as DNA methylation profiling and histone modification analysis were utilized to assess epigenetic alterations. Findings indicate that epigenetic modifications, including changes in DNA methylation and histone acetylation, play a significant role in regulating gene expression in response to stress. Certain stress-induced epigenetic changes were associated with enhanced tolerance to adverse conditions, suggesting a vital adaptive mechanism for plants. This research highlights the importance of epigenetics in understanding plant adaptation to environmental stress. The findings contribute to the growing body of knowledge regarding plant resilience mechanisms and may inform breeding programs aimed at developing stress-tolerant plant varieties